2016
DOI: 10.1111/jpi.12297
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits paraquat‐induced cell death in bovine preimplantation embryos

Abstract: Preimplantation embryos are sensitive to oxidative stress-induced damage that can be caused by reactive oxygen species (ROS) originating from normal embryonic metabolism and/or the external surroundings. Paraquat (PQ), a commonly used pesticide and potent ROS generator, can induce embryotoxicity. The present study aimed to investigate the effects of melatonin on PQ-induced damage during embryonic development in bovine preimplantation embryos. PQ treatment significantly reduced the ability of bovine embryos to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 68 publications
(91 reference statements)
3
25
0
Order By: Relevance
“…Our data indicates that a relative high level of melatonin (10 −3 mol/L) significantly reversed the reduction in blastocyst quality caused by AFB1 exposure during oocyte maturation. Similarly, previous studies also proved that melatonin has an essential function in improving embryo quality under normal IVM‐IVF conditions or stressed conditions …”
Section: Discussionmentioning
confidence: 55%
“…Our data indicates that a relative high level of melatonin (10 −3 mol/L) significantly reversed the reduction in blastocyst quality caused by AFB1 exposure during oocyte maturation. Similarly, previous studies also proved that melatonin has an essential function in improving embryo quality under normal IVM‐IVF conditions or stressed conditions …”
Section: Discussionmentioning
confidence: 55%
“…Our results showed that TO901317 treatment significantly inhibited PQ-induced apoptosis. Regarding the apoptotic signal pathway, JNK and p38 MAPK were described as the mediator of PQ-induced apoptosis [8] mainly through promoting Bax expression while suppressing Bcl-2 expression [10]. The increased Bax/Bcl-2 ratio leads to reduction of the mitochondrial transmembrane potential and release of proapoptotic protein from the mitochondria into the cytosol, ultimately resulting in apoptosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of mitogen-activated protein kinases (MAPKs) may be involved in the molecular mechanism of PQ-induced apoptosis [8]. MAPKs are protein Ser/Thr kinases that respond to various stressors and regulate cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin provided the most desirable characteristics, given its role as an antioxidant that prevents free radical‐mediated damage (Reiter et al, ). Numerous studies have shown that melatonin and its metabolic derivatives modulate the activity of many pro‐ and anti‐oxidant enzymes, leading to a reduction in oxidative damage to lipids, proteins, and DNA (Manchester et al, ; Pang et al, ). More specifically, melatonin can directly benefit sperm characteristics, including enhanced total motility, progressive motility, and viability rates (Ortiz et al, ; Succu et al, ; Ashrafi et al, ); increased sperm membrane and DNA integrity (Succu et al, ; Ashrafi et al, ); reduced membrane lipid peroxidation (Jang et al, ; Ashrafi et al, ); and modulation of sperm capacitation (Casao et al, ).…”
Section: Introductionmentioning
confidence: 99%